2023
DOI: 10.1093/mnras/stad648
|View full text |Cite
|
Sign up to set email alerts
|

Robustness measures for molecular detections using high-resolution transmission spectroscopy of exoplanets

Abstract: Ground-based high-resolution transmission spectroscopy has emerged as a promising technique for detecting chemicals in transiting exoplanetary atmospheres. Despite chemical inferences in several exoplanets and previous robustness studies, a robust and consistent detrending method to remove telluric and stellar features from transmission spectra has yet to be agreed upon. In this work we investigate the robustness of metrics used to optimise PCA-based detrending for high-resolution transmission spectra of exopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 85 publications
3
19
0
Order By: Relevance
“…Studies on the robustness of molecular detections by HRS of exoplanets demonstrate that some detrending methods may induce false positive or inflated detections (Cheverall et al 2023). In their case study on HD 209458b, HCN, NH 3 , and CH 4 were not observed by Cheverall et al (2023). However, a signal for CH 4 can be detected if the telluric contamination is not correctly removed.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the robustness of molecular detections by HRS of exoplanets demonstrate that some detrending methods may induce false positive or inflated detections (Cheverall et al 2023). In their case study on HD 209458b, HCN, NH 3 , and CH 4 were not observed by Cheverall et al (2023). However, a signal for CH 4 can be detected if the telluric contamination is not correctly removed.…”
Section: Discussionmentioning
confidence: 99%
“…For such a more finely tuned approach to selecting the number of PCs to remove, it would be appropriate to develop a quantitative metric to indicate how many is "enough." This is not trivial; CCF signals can be spuriously overoptimized to particular models or velocities (see, e.g., Cabot et al 2019;Cheverall et al 2023), and searching for correlations between the LSVs and physical components of the data requires a comprehensive record of such components. Air mass and humidity appear to be prevalent quantities captured by the SVD in these data, but information about, e.g., the seeing or dew point was not available, yet it may still impact the data.…”
Section: Sensitivity Of the Post-eclipse Data To The Number Of Pcs Re...mentioning
confidence: 99%
“…6 This data set has been previously used to successfully detect water vapor and to infer the hazy nature of the atmosphere of this hot Jupiter (Alonso-Floriano et al 2019;Sánchez-López et al 2019. In addition, it was used by Cheverall et al (2023) as a case study for evaluating different preparing methods for CCF analysis. We used the data from the NIR channel's fiber A (focused on the target star HD 189733), which covers the spectral range 0.96-1.71 μm in 28 echelle orders at a spectral resolution of »  80,400.…”
Section: Observationsmentioning
confidence: 99%
“…The preparing steps are often not described exhaustively, sometimes making reproducibility and comparisons difficult. This need for a consistent, reproducible, and robust preparation technique has already been raised (Cabot et al 2018;Cheverall et al 2023). Similarly, how the likelihood function terms are modified can vary significantly between authors-especially regarding the modification of the forward models.…”
Section: Introductionmentioning
confidence: 99%